DAMPAK GEMPA BUMI TERHADAP PEMBELAJARAN PAI DI SD NEGERI NO 1 SASENDE KECAMATAN MALUNDA KABUPATEN MAJENE - Fahrurrozih, Muhammad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The research aims: 1) To find out the impact caused by the earthquake, 2) to find out PAI learning at SD Negeri No. 1 Sasende, Malunda sub-district, Majene district after being affected by the earthquake, 3) To find out whether there was an impact of the earthquake that affected PAI learning in elementary school Negeri No. 1 Sasende, Malunda sub-district, Majene regency. This research is quantitative research with an ex post facto type of research. With a purposive sampling data collection technique, 15% of the entire population, namely 39 people out of 261 people. Data collection techniques use questionnaires. Based on research conducted at SD Negeri No. 1 Sasende, it was found that: 1) the impacts caused by the earthquake included: damage to classes, damage to the library, trauma to students, and failure to carry out the teaching and learning process from the start of the earthquake to 1 month long, 2) PAI learning at that time could not last for 45 days because the entire community had to seek shelter in a safer place, 3) there was an impact of the earthquake on PAI learning at SD Negeri No. 1 Sasende, Malunda subdistrict, Majene district. with (tcount > ttable = 2.352 > 2.026). proves that the contribution of the impact of the earthquake to PAI learning at SD Negeri No. 1 Sasende is 2.4%.